Tratamiento comunitario asertivo: práctica, consideraciones éticas y rol del trabajador social - Morago, Pedro (Cuadernos de Trabajo Social, 2006)
Initially developed in the United States, the Assertive Community Treatment (ACT) has expanded to Canada, Sweden and the UK and is being implemented in an increasing number of countries, amongst them Spain. While supported by solid scientific evidence, ACT has also being criticised for being too intrusive into the private lives of individuals with mental health problems. Recent literature suggests that a collaborative approach may be appropriate in order to resolve the ethical dilemmas posed by ACT as well as to promote social integration of people with serious mental illness. Such objectives require the active involvement within ACT teams of social workers, professionals who possess the specific skills needed to promote empathy and integration according to a bio-psychosocial approach to mental health.